2018
DOI: 10.1002/mgg3.498
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing of nevoid basal cell carcinoma syndrome families and review of Human Gene Mutation Database PTCH1 mutation data

Abstract: BackgroundNevoid basal cell carcinoma syndrome (NBCCS) is an autosomal dominant disorder with variable expression and nearly complete penetrance. PTCH1 is the major susceptibility locus and has no known hot spots or genotype–phenotype relationships.MethodsWe evaluated 18 NBCCS National Cancer Institute (NCI) families plus PTCH1 data on 333 NBCCS disease‐causing mutations (DM) reported in the Human Gene Mutation Database (HGMD). National Cancer Institute families underwent comprehensive genomic evaluation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 46 publications
(79 reference statements)
3
28
0
Order By: Relevance
“…Undén et al found that the expression level of PTCH mRNA was overexpressed in BCC cells compared with nontumor epidermal cells, which was similar to our finding that PTCH1 was upregulated in BCC patients [22]. Interestingly, numerous researchers pointed out that approximately 90% of function mutations in PTCH1 were [24]. A recent investigation has reported that PTCH1 had two mutational statuses (germinal and somatic mutation).…”
Section: Discussionsupporting
confidence: 88%
“…Undén et al found that the expression level of PTCH mRNA was overexpressed in BCC cells compared with nontumor epidermal cells, which was similar to our finding that PTCH1 was upregulated in BCC patients [22]. Interestingly, numerous researchers pointed out that approximately 90% of function mutations in PTCH1 were [24]. A recent investigation has reported that PTCH1 had two mutational statuses (germinal and somatic mutation).…”
Section: Discussionsupporting
confidence: 88%
“…Gorlin-Goltz syndrome (GGS) was first described in 1960 and is alternatively termed Gorlin syndrome, nevoid basal cell carcinoma syndrome (NBCCS), or basal cell nevus syndrome [11]. GGS/NBCCS is a rare condition with an incidence reported as high as 1 in 19,000 births and with nearly complete penetrance but variable expression [11][12][13][14][15][16]. The most frequently observed characteristic is basocellular carcinoma -often with an early onset during the first and second decades of life [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…GGS/NBCCS is a rare condition with an incidence reported as high as 1 in 19,000 births and with nearly complete penetrance but variable expression [11][12][13][14][15][16]. The most frequently observed characteristic is basocellular carcinoma -often with an early onset during the first and second decades of life [12][13][14][15][16]. The inheritance pattern of GGS/NBCCS is predominantly autosomal dominant [11][12][13][14][15][16]; however, penetrance of the phenotypes is variable in affected relatives [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterozygous germline PTCH1 mutations cause Gorlin syndrome (OMIM 109400, Gorlin-Goltz syndrome, nevoid basal cell carcinoma, or basal cell nevus syndrome), an autosomal dominant disorder that predisposes affected individuals to developmental defects and tumorigenesis (Kimonis et al, 1997, Gorlin 2004, Pellegrini et al, 2017. Dozens of pathogenic variants in the PTCH1 gene include deletions or insertions, (multi)exon or large-scale deletions or rearrangements resulting in frameshifts, nonsense mutations leading to premature stops, missense, splice-site mutations, and deep intronic variants that alter splicing (Hahn et al, 1996, Lindström et al, 2006, Gianferante et al, 2018. A careful analysis revealed that high frequency of mutations is clustered into the intracellular and two extracellular loops (Lindström et al, 2006).…”
Section: Ptch1 Genementioning
confidence: 99%